Lower Bounds for Gas Turbines Aircraft Engines - Jemmali, Mahdi; Bani Melhim, Loai Kayed; Alharbi, Sayer Obaid B.; Bajahzar, Abdullah Saeed (Communications in Mathematics and Applications, 2019)
Turbine maintenance process is performed periodically at predefined time slots to replace certain turbine parts by new or refurbished parts. The developed heuristics will address the scheduling of turbine maintenance problem to maximize crafts operation time. Scheduling is based on the life span of the replaced parts. Mathematical modeling for the lower bounds of the aircraft turbine maintenance problem will be presented to achieve the desired goal. this study is based on three heuristic categories, the randomized lower bounds, the utilization of the iterative methods solving the subset sum problems and the repeating of the resolution of the knapsack problems.